1999
DOI: 10.1046/j.1365-313x.1999.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of two gene subfamilies encoding the plasma membrane H+‐ATPase in Nicotiana plumbaginifolia reveals the major transport functions of this enzyme

Abstract: Summary The plasma membrane H+‐ATPase couples ATP hydrolysis to proton transport, thereby establishing the driving force for solute transport across the plasma membrane. In Nicotiana plumbaginifolia, this enzyme is encoded by at least nine pma (plasma membrane H+‐ATPase) genes. Four of these are classified into two gene subfamilies, pma1‐2‐3 and pma4, which are the most highly expressed in plant species. We have isolated genomic clones for pma2 and pma4. Mapping of their transcript 5′ end revealed the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 37 publications
4
74
0
4
Order By: Relevance
“…Therefore, it is likely that in active proteoid roots, an enhanced expression of a special isoform (or isoforms) of plasma membrane H ϩ ATPase is induced to meet the high demand of the cells to extrude H ϩ . Such a tissue-, organ-, or cell-specific expression of isoforms of H ϩ ATPase has been reported by a number of investigations (DeWitt et al, 1991;Michelet et al, 1994;Moriau et al, 1999) and summarized as a "tissue-specific expression model" in which enzymatically equivalent enzymes are expressed in different cells by promoters providing controlled expression levels ideally suited for a cell's particular needs (Palmgren and Harper, 1999).…”
Section: Atpase In Active Proteoid Roots To P Deficiencymentioning
confidence: 93%
“…Therefore, it is likely that in active proteoid roots, an enhanced expression of a special isoform (or isoforms) of plasma membrane H ϩ ATPase is induced to meet the high demand of the cells to extrude H ϩ . Such a tissue-, organ-, or cell-specific expression of isoforms of H ϩ ATPase has been reported by a number of investigations (DeWitt et al, 1991;Michelet et al, 1994;Moriau et al, 1999) and summarized as a "tissue-specific expression model" in which enzymatically equivalent enzymes are expressed in different cells by promoters providing controlled expression levels ideally suited for a cell's particular needs (Palmgren and Harper, 1999).…”
Section: Atpase In Active Proteoid Roots To P Deficiencymentioning
confidence: 93%
“…We can expect rapid advances in our understanding of the function of P-type pumps with the combination of physiological and molecular genetic approaches in the coming years. Reporter gene analyses (Haseloff, 1999;Moriau et al, 1999) and DNA microarray technology (Schena et al, 1995) will be employed on a large scale to study gene expression as a function of space, time, and environmental conditions. In the different subfamilies, knockout mutants for all members will be isolated and multiple knockouts will be generated by crossing these lines (Young et al, 2001).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…It has been shown that various genes are expressed in the same organ. Moreover, even within the same cell type at the same developmental stage, at least two H + -ATPase genes are expressed (Harms et al, 1994;Hentzen et al, 1996;Moriau et al, 1999). In N. plumbaginifolia two different plasma membrane H + -ATPase genes, PMA2 and PMA4, are expressed in guard cells (Moriau et al, 1999).…”
mentioning
confidence: 99%